2014
DOI: 10.5897/ajpp2014.4122
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of medication use among low risk pregnant women: A drug utilization study

Abstract: This study aimed to characterize the profile of medication consumption by low risk pregnant women and to correlate it with sociodemographic characteristics of this population. A cross-sectional descriptive study was conducted in the Reference Center of Women's Health in the Brazilian municipality of Ribeirão Preto. This study included women which were at least in the 32nd week of the gestation period. Data related to sociodemographic characteristics of the pregnant women and to their pregnancy and medication c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
3
2
2
Order By: Relevance
“…This finding was in line with a study conducted in northern Ethiopia [8] where high number of drugs was used from this category. However, this finding had shown a gap from the study conducted in Sao Paulo, Brazil [28] and Fiche hospital, Ethiopia [29] in which only 20.55% and 20.83%, respectively, were from category A. The study conducted in a tertiary care hospital, India indicated that 91.13% of drugs used during pregnancy were from this category and was found slightly higher than the present finding [30].…”
Section: Discussioncontrasting
confidence: 92%
See 2 more Smart Citations
“…This finding was in line with a study conducted in northern Ethiopia [8] where high number of drugs was used from this category. However, this finding had shown a gap from the study conducted in Sao Paulo, Brazil [28] and Fiche hospital, Ethiopia [29] in which only 20.55% and 20.83%, respectively, were from category A. The study conducted in a tertiary care hospital, India indicated that 91.13% of drugs used during pregnancy were from this category and was found slightly higher than the present finding [30].…”
Section: Discussioncontrasting
confidence: 92%
“…This was similar with the study conducted in Adama [1], northern Ethiopia [8] and Banglore [36]. Studies indicated that there was a practice of prescribing drugs from category X in Omani (0.3%) [9], in Brazil (0.03%) [28], in Jimma, Ethiopia (7.4%) [10], in Bahirdar, Ethiopia (5.5%) [12], and in United States (4.6%) [11]. …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…A similar trend of less drug prescription with increased number of visits to the health facilities was observed in the study conducted in Brazil [22]. This could be due to the fact that the more frequent the visiting the better is the counseling of the health providers for the pregnant women regarding the issues related to different aspects of pregnancy.…”
Section: Discussionsupporting
confidence: 74%
“…This might have helped the pregnant women to manage their health problem without actually consuming drugs. In contrast, other studies reported the utilization of more drugs by the pregnant woman with more frequent prenatal visits [22, 23]. …”
Section: Discussionmentioning
confidence: 85%